2008
DOI: 10.4049/jimmunol.180.7.4656
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Control of Integrin Expression Regulates Th2 Effector Homing

Abstract: Integrin CD18, a component of the LFA-1 complex that also includes CD11a, is essential for Th2, but not Th1, cell homing, but the explanation for this phenomenon remains obscure. In this study, we investigate the mechanism by which Th2 effector responses require the LFA-1 complex. CD11a-deficient T cells showed normal in vitro differentiation and function. However, Th2 cell-dependent allergic lung disease was markedly reduced in CD11a null mice and wild-type mice given LFA-1 inhibitors, whereas control of infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
22
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 56 publications
3
22
0
Order By: Relevance
“…These studies suggest that the mechanisms, by which cell adhesion molecules regulate tissue fibrosis, could be through the regulation of Th1 and Th2 cell infiltration. Two studies have demonstrated that loss of L-selectin and/or ICAM-1 function inhibited Th2 cell immigration, inducing Th1 cell infiltration in the allergic lung disease model (46, 47). In addition, Loss of P-selectin, E-selectin, and/or PSGL-1 function prevents Th1 cell infiltration and induce Th2 cell immigration in the cutaneous delayed-type hypersensitivity and allergic lung disease models (11, 48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies suggest that the mechanisms, by which cell adhesion molecules regulate tissue fibrosis, could be through the regulation of Th1 and Th2 cell infiltration. Two studies have demonstrated that loss of L-selectin and/or ICAM-1 function inhibited Th2 cell immigration, inducing Th1 cell infiltration in the allergic lung disease model (46, 47). In addition, Loss of P-selectin, E-selectin, and/or PSGL-1 function prevents Th1 cell infiltration and induce Th2 cell immigration in the cutaneous delayed-type hypersensitivity and allergic lung disease models (11, 48).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, blocking studies using anti-LFA-1 or PSGL-1 mAbs have suggested that Th cell migration mainly depends on LFA-1 or PSGL-1, though virtually all lymphocytes express LFA-1 and PSGL-1 (11, 46). Although the mechanism, by which Th cell infiltration is regulated by LFA-1 and PSGL-1, remains unclear, our present study is the first to suggest that expression intensity of LFA-1 and PSGL-1 contributes to Th cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this finding, in vivo adherence of adoptively transferred alloreactive Th1 cells to the lung is decreased in ICAM-1 −/− mice (Dixon et al , 2000). By contrast, allergic lung disease is reduced in mice deficient for LFA-1, an ICAM-1 counterreceptor, which is due to markedly impaired recruitment of Th2 cells to the lungs (Lee et al , 2008). Similarly, ICAM-1 deficiency attenuates skin fibrosis and leukocyte infiltration with decreased Th2 cytokine expression in the affected skin from tight-skin mouse, a model of systemic sclerosis (Matsushita et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although LFA-1 has been reported to be required for optimal T-cell activation using polyclonal or antigen specific activation of T cells 24,34,35,40,60 , there are also several reports demonstrating that LFA-1 is either dispensable for T-cell activation 36,55,56,60 or is required for low but now not high concentrations of antigen 36 . Using an in vitro model that more closely mimics those early immunological events that are thought to occur during the priming, polarization and expansion of naïve T-cells to yield colitogenic effector cells in lymphopenic mice, we failed to demonstrate a major co-stimulatory role for LFA-1.…”
Section: Discussionmentioning
confidence: 99%